PENGARUH RISIKO KREDIT DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PERBANKAN PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BEI ( 2012-2016 ) - Chairul Anam (MARGIN ECO, 2018)
Banking financial performance can be measured by evaluating or analyzing financial statements. Financial position, financial information and company performance in a previous period will be used as a basis for predicting future financial performance. Regarding the bank's financial performance, the ratio used to measure financial performance is the profitability ratio. One of the profitability ratios used for financial performance is ROA (Return on Assets). And now the state of unstable financial performance results in a lack of optimally generated profits, indicated by the average ROA of 2012 recorded at 2.09% and experiencing a significant decline of 1.29% in 2013, then a decline in returns of 1.08% in 2014 and a decline of up to a value of 0.96% in 2015, until finally experiencing a slight increase of 1.51% in 2016. This shows the movement of ROA growth is less stable and will affect the level of profitability and performance banking finance. This study aims to analyze the effect of variable Non Performing Loans (NPL) and the effect of Loan to Deposits Ratio (LDR) on Return On Assets (ROA). The results of the test results using the SPSS program obtained Y = 5,159 - 1,306X1 - 0,021X2. Estimated results with multiple linear regression models indicate that the fundamental variables namely Non Performing Loan and Loan to Deposite Ratio together have a strong relationship with Return On Assets. By looking at the determination coefficient adjusted R square = 0.428 shows that the NPL and LDR variables have the ability to explain the movement pattern of ROA of 42.8% while the remaining 57.2% is explained by other independent variables. Keyword: credit risk, liquidity and banking financial performance